Differences in the solubility of CaCO3 from blood clam shells and Ca(OH)2 as a candidate pulp capping material - Saraswati, Widya; Pribadi, Nirawati; Mutmainnah, Chaerun (Universitas Airlangga, 2023)
Background: Calcium hydroxide (Ca(OH)2) is the gold standar in pulp capping treatment because the biocompatibility and capability to stimulate hard tissue formation and also antibacterial effect. However, this compound has the disadvantage of being easily soluble in saliva which will increase the risk of leakage in the cavity. Another alternative pulp capping material is calcium carbonate from blood clam shells. Blood clam shells contain 98% CaCO3, CaCO3 has low solubility and is difficult to dissolve in water due to the large ions on Ca2+ and CO32- so that the attractive force between these ions is very strong and finally H2O is not able to break down the CaCO3 compound to be dissolved. Purpose: Explained the differences in the solubility of calcium carbonate from blood clam shells and calcium hydroxide as candidates pulp capping materials. Methods: This research is a laboratory experimental study with a pretest-posttest control group design method. The samples consisted of 12 pieces of Ca(OH)2 and CaCO3 then divided into 2 groups and given treatment. Group 1 CaCO3 immersed in 1 day, group 2 Ca(OH)2 immersed in 1 day, group 3 CaCO3 immersed in 7 days, and group 4 Ca(OH)2 immersed in 7 days. Solubility is calculated according to the solubility formula. Data testing with Anova-Welch. Results: There was a significanly difference in the solubility rate between the CaCO3 dan Ca(OH)2 groups immersed for 1 day and 7 days on the Anova-Welch results (p<0.05). Conclusion: The solubility of CaCO3 in blood clam shells is lower than the solubility in Ca(OH)2.)